2001
DOI: 10.1016/s0893-133x(01)00282-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LSD on Prepulse Inhibition and Spontaneous Behavior in the Rat A Pharmacological Analysis and Comparison between Two Rat Strains

Abstract: The goal of the present study was to better delineate the mechanisms of action of the prototypical hallucinogen LSD. LSD (0.03, 0.1 and 0.3 mg/kg, s.c.) Delineation of the neurobiological mechanisms underlying the profound effects of hallucinogens on perception, mood, and thought processes has been the subject of great interest over the years. There is now increasing evidence that the two major classes of hallucinogens, the indolamines (e.g., LSD) and the phenethylamines (e.g., DOM and DOI) share a common si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 50 publications
9
63
1
Order By: Relevance
“…Thus, the effects of LSD and psilocybin on the acoustic startle response and its modulation were quite similar. Additionally, the disruption of PPI induced by psilocybin in humans at a short ISI (30ms) was prevented by administration of a 5-HT 2A receptor antagonist (69), consistent with similar preclinical studies of LSD (41). In contrast to the findings with LSD and psilocybin, DMT or ayahuasca had no Schmid et al Effects of LSD 13 effects on PPI, startle reactivity, or habituation in humans (19,70).…”
Section: Sensorimotor Gating Of the Acoustic Startle Responsesupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, the effects of LSD and psilocybin on the acoustic startle response and its modulation were quite similar. Additionally, the disruption of PPI induced by psilocybin in humans at a short ISI (30ms) was prevented by administration of a 5-HT 2A receptor antagonist (69), consistent with similar preclinical studies of LSD (41). In contrast to the findings with LSD and psilocybin, DMT or ayahuasca had no Schmid et al Effects of LSD 13 effects on PPI, startle reactivity, or habituation in humans (19,70).…”
Section: Sensorimotor Gating Of the Acoustic Startle Responsesupporting
confidence: 65%
“…Specifically, prepulse inhibition (PPI) of the acoustic startle Schmid et al Effects of LSD 4 response serves as an operational measure of sensorimotor gating that can be assessed in animals and humans (35). PPI is impaired in schizophrenia and also in prodromal states and early phases (35)(36)(37)(38), and hallucinogens like LSD acutely disrupt PPI in animals (39)(40)(41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ouagazzal et al (2001) demonstrated that the decrease in PPI induced by LSD in rats also was mediated by 5-HT 2A receptors. The disruption of PPI induced by LSD in Sprague-Dawley rats was completely blocked by pretreatment with the highly selective 5-HT 2A antagonist M100907.…”
mentioning
confidence: 90%
“…86 In humans, psilocybin disrupts PPI at short interstimulus intervals (ISIs), but has no effect at medium ISIs, and, notably, enhances PPI at long ISIs. 87,88 In rodents, some, but not all, of these studies suggest that psychedelics disrupt PPI at short, medium and long ISIs. 89−91 It is also worth noting that, while both lisuride and LSD disrupt PPI in rats, pretreatment with the 5-HT 2A antagonist α-phenyl-1-(2-phenylethyl)-4-piperidinemethanol (MDL11939) reverses the effect of LSD, but not that of lisuride.…”
Section: Acs Chemical Neurosciencementioning
confidence: 97%